URGENSI ILMU AL-JARH WA AT-TA’DIL DALAM MENJAGA KEMURNIAN HADIS - Moh Rokib (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
Hadith is the second source of Islamic teachings after the Qur'an which has an important position in determining the validity of Islamic laws and teachings. To maintain the purity of the hadith, an in-depth study of the narration of the hadith is needed, especially in assessing the credibility of the narrators. One of the sciences that plays an important role in this process is the science of Al-Jarḥ wa At-Ta'dīl, which is a science that discusses the assessment of the narrator of the hadith, both in the form of criticism (jarḥ) of shortcomings and praise (ta'dīl) for their justice and accuracy. This study uses a library research method with a qualitative approach, based on the analysis of literature from various scientific sources. The results of the study show that Al-Jarḥ wa At-Ta'dīl has a strong shari'a basis both from the Qur'an and the hadith of the Prophet, and contains a number of conditions for scholars who want to criticize and praise the narrator. This study confirms that the validity of the hadith depends heavily on the integrity of the narrators, which can only be determined through the strict scientific method as stipulated in the Science of Al-Jarḥ wa At-Ta'dīl